Pengaruh Pemberian Mesenchymal Stem Cells Wharton's Jelly terhadap Ekspresi Gen Sirtuin 1 pada Tikus Model Alzheimer - Aizah, Havina Nurul; Yanis, Amel; Ali, Hirowati; Tofrizal, Tofrizal; Ilmiawati, Cimi; Arisanty, Dessy (Faculty of Medicine, Universitas Andalas, 2023)
Mesenchymal Stem Cells Wharton's Jelly (MSC-WJ) has become a new hope for Alzheimer's disease due to its capability to suppress Amyloid-beta (Aβ) plaques formation. It is found that people with Alzheimer's disease have a lower expression of Sirtuin-1 because of the oxidative stress that was produced by Aβ plaques. Objective: To observe the Sirtuin-1 gene in Alzheimer's disease rat models that AlCl3 was inducing after being given MSC-WJ. Methods: This was an experimental study with a post-test-only control group design, including three groups with a total sample of 18 samples of Alzheimer RNA rat models. Group-1without AlCl3 and MSC-WJ; Group-2 with AlCl3; Group-3 AlCl3 and MSC-WJ. Mean value of the Sirtuin-1 gene was obtained by the Image-J application using a semiquantitative method which was then tested using the One Way ANOVA test. The study was significant if the p-value < 0,05. Results: This study found that the mean ± standard error value of the Sirtuin-1 gene in three groups were 0.18±0.04; 0.16±0.03; and 0.36±0.06 respectively. The statistical test showed a significant difference between the three groups (p = 0.014). Conclusion: There was an increased Sirtuin 1 gene expression in Alzheimer’s rat Model after being given Mesenchymal Stem Cells Wharton’s Jelly.Keywords: Alzheimer, MSC-WJ, Sirtuin-1